2021
DOI: 10.1186/s12889-021-10401-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of the state of emergency over COVID-19 for non-permanent workers: a Nationwide follow-up study in Japan

Abstract: Background The outbreak of COVID-19 has caused mental health problems and increased unemployment due to the economic recession. This survey aimed to assess the psychological impact of the state of emergency. We estimated changes in mental health, quality of life, and unemployment experience for general workers during the first COVID-19 outbreak in Japan. Methods We conducted a nationwide follow-up study. During the periods of March 26 to April 6, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 23 publications
1
17
3
Order By: Relevance
“…The findings echoed previous studies showing mental health in temporary employees was not deteriorated in the COVID‐19 pandemic. 4 , 5 Other job characteristics and personal circumstances may be more important factors regarding vulnerability in response to COVID‐19. As recent studies have suggested, regardless of the employment contract present, “working” provided a better outcome compared to unemployment or loss of job in the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings echoed previous studies showing mental health in temporary employees was not deteriorated in the COVID‐19 pandemic. 4 , 5 Other job characteristics and personal circumstances may be more important factors regarding vulnerability in response to COVID‐19. As recent studies have suggested, regardless of the employment contract present, “working” provided a better outcome compared to unemployment or loss of job in the COVID‐19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…As recent studies have suggested, regardless of the employment contract present, “working” provided a better outcome compared to unemployment or loss of job in the COVID‐19 pandemic. 3 , 4 , 5 A possible reason for finding no significant association with newly developed suicidal ideation may be that the pandemic has been more burdensome based on personal background (e.g., age, family) or industry than on employment status. Although the economic situation has been worsened, it is unclear whether temporary employees are unique to be disadvantaged workers in such a situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The socio-economic status of respondents-all of them self-reported middle-class women-should also not be underestimated as a key factor in women's solution-seeking behaviour. Recent surveys on the impacts of socio-economic factors on psychological and emotional health in the early phases of the COVID-19 pandemic in the general population in Japan show that low-income and precarious employment are negatively related to helpseeking behaviours, especially among younger women (Nagasu et al 2021;Sugaya et al 2021;Yamamoto et al 2020), also affecting their mental health (Saito et al 2021). This is identified as a category that is less inclined to seek emotional care and support (Ueda et al 2020).…”
Section: Discussion: a Trend Toward Spiritual Coping Mechanisms Durin...mentioning
confidence: 99%
“…Blustein et al believe that people without a stable job will experience chronic stress and uncertainty [3], which makes them face the risk of mental health, physical and relationship problems. In fact, a study conducted in Japan shows that the mental health of non-permanent workers would not be negatively affected after the Japanese government declared the state of emergency [7]. However, unemployment is an important factor affecting the mental health of ordinary workers.…”
Section: Consequence Of Epidemic Situationmentioning
confidence: 99%